Characteristics of Physical Test of Puffer Fish (Arathon reticularis) Leather With Various Types of Tanning Materials - Wibowo, Lukas M. S. Ari (Fisheries Department, Faculty of Agriculture, Universitas Gadjah Mada, 2015)
Tanning aims to avoid stifffness and hardness of leather, so leather will be flexible when it is dry and it can also be durable. Tanning will directly change the characteristics of leather, especially its appearance, handling and smell. With tanning, leather is expected to endure heat better than skin or raw leather. In Indonesia, puffer fish leather tanning is still being studied, so initial research by using three types of tanning,i.e vegetable, chrome, and formalin is required. The physical characteristics of the three types of tanning were tested, i.e. tensile strength, elongation, sewing strength, and tear strength. The results of comparison of tensile strength and elongation in skip group; and tear strength and sewing strength in leather group of tanning (Vegetable, wet blue, and formalin) show significannce scores of 0,001; 0,000; 0,000; and 0,000 < 0,05, respectively. It showed that there were differences in tensile strength, elongation, sewing strength, and tear strength. This research entitled Characteristics of Physical Test of Puffer Fish (Arothon reticularis) Leather with Various Types of Tanning Materials is expected to contribute required data in puffer fish leather tanning in order to produce tanned puffer fish leather for desired purposes.